Assessing L1 Competence Decline among Yoruba-English Bilingual Undergraduates at Usmanu Danfodiyo University, Sokoto - Abdulahi Olarewaju Aremu (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2024)
This study sets out to investigate the extent of lack of competence in Yoruba among Yoruba-English bilingual undergraduates at Usmanu Danfodiyo University, Sokoto. A mixed-methods approach was adopted for interpretations to be drawn based on the combined strengths of both datasets (i.e., quantitative and qualitative data). 123 participants, 76 males, and 47 females, completed the questionnaires, while interviews were conducted with 11 participants, 8 males and 3 females, to validate their self-assessment and gain a deeper understanding of their language abilities through open-ended questions and direct observations. Quantitative data analysis involved frequency and percentage calculations, with subsequent interpretation and discussion. Qualitative analysis entailed transcribing the interviews, interpreting the responses, and discussing the findings. Both quantitative and qualitative results were compared, and the extent to which they confirmed each other was established. Findings show that a substantial number of participants exhibited a moderate ability in their L1. Although both the current and the earlier studies point towards the decline in Yoruba competence among the young generation, particularly compared to the older generation, the current study delves deeper into participants’ competence levels through various tasks like speaking, translating, and interpreting idioms.  The coverage of areas such as numeracy, days of the week, and months of the year is unique to this study as they have not been previously explored.